THE EFFECT OF PRICE AND PROMOTION ON PURCHASE DECISION AT BAKPIA KURNIA SARI - Sjukun Sjukun; Lalu Supardin; Yusuf Taufik (PENANOMICS: International Journal of Economics, 2022)
This study aims to examine the effect of price and promotion on purchase decision at Bakpia Kurnia Sari. The respondents in this study were consumers in Yogyakarta. The number of respondents in this study were 100 respondents. Sampling was done by purposive sampling technique. This study uses multiple linear regression analysis technique with SPSS as an analytical tool. The results of the multiple linear regression test show that: 1) Price partially has a significant effect on purchase decision at Bakpia Kurnia Sari. 2) Promotion partially has a significant effect on purchase decision at Bakpia Kurnia Sari.